2020
DOI: 10.3946/kjme.2020.167
|View full text |Cite
|
Sign up to set email alerts
|

Negative school experiences of Late Millennial Korean medical students: a qualitative study using the critical incident technique

Abstract: Purpose: Today's students have distinctive generational characteristics and increased psychopathology and generational tension. The authors investigated the negative experiences of Late Millennial students in medical school to draw implications for student support. Methods: The authors explored medical students' negative experiences using the critical incident technique. The authors conducted semi-structured in-depth interviews with 13 medical students, between February and May 2016. The authors focused on occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The principal ndings in this study were that the CIs were predominantly related to clinical cases of non-COVID pathologies that occurred in a public hospital and caused negative emotions. This is similar to the ndings of another study that describes CIs related to negative experiences in students before pandemics [7] and highlights that the conditions of clinical teaching during internships are complex and independent of the actual crisis. This is an important issue because determines that medical schools should be aware of the existence of moral distress and challenges to psychological safety in clinical settings in our country.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The principal ndings in this study were that the CIs were predominantly related to clinical cases of non-COVID pathologies that occurred in a public hospital and caused negative emotions. This is similar to the ndings of another study that describes CIs related to negative experiences in students before pandemics [7] and highlights that the conditions of clinical teaching during internships are complex and independent of the actual crisis. This is an important issue because determines that medical schools should be aware of the existence of moral distress and challenges to psychological safety in clinical settings in our country.…”
Section: Discussionsupporting
confidence: 84%
“…This idea does not emerge in the CI analysis. In the literature, there are some descriptions of how the changes in health systems de ne new aspects to consider in the teaching process, such as humanism in the profession [21,22,35] or the effects of cognitive load on clinical decision-making [7] . Further research could examine these elements from the interns' perspectives in our country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For medical students, building new relationships is crucial for adapting to the new academic environment and is expected to involve significant effort [ 8 ]. Previous studies have reported that medical students tend to form competitive relationships and prioritize business-like relationships over socializing with peers in the rigorous academic environments of medical school [ 9 ].…”
Section: Introductionmentioning
confidence: 99%